Evaluation of nutritional status in patients with end-stage renal disease in hemodialysis using principal component analysis - Saenz Pardo Reyes, Erika; Housni, Fatima Ezzahra; López-Espinoza, Antonio; Martinez Moreno, Alma Gabriela; Padilla Galindo, Maria del Rocio (Progress in Nutrition, 2020)
The evaluation of nutritional status in patients with end-stage renal disease in hemodialysis is composedof a large number of measurements that complicate their execution. Therefore, the objective of this studyis to reduce the number of variables through the principal component analysis (PCA). For this, a PCA wasperformed with 10 variables of the nutritional diagnosis in patients with hemodialysis: Energy Intake, ProteinIntake, IBM,% UBW,% SBW,% MUAC, cAMA,% TCF, HGS and TLC as well as the age of the patients. Theresults show that PCA matrix with orthogonal rotation Varimex yielded four main components of the evaluationof the nutritional status of renal disease in patients with end-stage hemodialysis, whose value was greaterthan 0 and explains the 79.91% of the total variance. The first factor was called body composition status, whichis composed of cAMA (r = 0.9138), IBM (r = 0.8755),% MUAC (r = 0.8681) and% SBW (r = 0.6238). In thesecond factor called nutritional risk, a correlation was observed with energy intake (r = -0.8934), protein intake(r = -0.8752) and %TCF (0.5040). The third component called functional status risk is composed of age (r =0.9022) and HGS (r = 0.8508). The fourth factor, called body composition stability, was correlated with %UBW(r = 0.7456) and %TCF (r = 0.5825). The results of this study will allow reducing the number of variables for thepreparation of a nutritional diagnosis in hemodialysis patients. From many to one of the four main components:1) body composition status, 2) nutritional risk, 3) functional status risk or 4) body composition stability.